Learn from the Experts about Being Performance-First Todd DeCapua - DeCapua, Todd (O'Reilly Media, Inc., 2018)
Learn from the Experts is a series where we sit down with leading industry practitioners and ask them for real-world stories and examples of how they're using technology in their everyday work. In this interview, Ally MacDonald talks to Todd DeCapua about how companies can make the shift to being "performance-first" at both a technical and organizational level. Todd DeCapua is a technology evangelist, passionate senior software executive and business leader. Some of his roles/titles include: Senior Director of Technology and Product Innovation at CSC, Chief Technology Evangelist at Hewlett-Packard Enterprise, Co-Founder of TechBeacon.com, VP of Innovation and Strategy Board Member at Vivit Worldwide, Independent Board Member at Apposite Technologies, and Member of the Performance Advisory Council. He is also a very active online author [@AppPerfEng on Twitter] and contributor and co-author of the O'Reilly published book titled, Effective Performance Engineering